PENGARUH RELATIONSHIP MARKETING TERHADAP PENINGKATAN KEPUASAN PELANGGAN PADA PT. TELKOMSEL SUMBAWA - Ika Fitriyani; Diah Arum Pratiwi (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to know: (1) the effect of trust toward increasing customers at PT. Telkomsel Indonesia, (2) the effect of commitment toward increasing customers at PT. Telkomsel Sumbawa, (3) the effect of trust and commitment toward increasing customers at PT. Telkomsel Indonesia. The type of this study was associative study. The data used in this study was primary data. The numbers of samples in this study were 30 samples. The method used to collect data was through questionnaires. The data analysis technique used was multiple linear regression. Results of study showed that partially trust did not have effect toward increasing customers at PT. Telkomsel Indonesia, it was based on the t-value < t-table (1.725 < 2.052) with significance value of 0.95 > 0.05, then commitment had effect toward increasing customers at PT. Telkomsel Indonesia, it was based on the value of t-value > t-table (2.921 > 2.052) with a significance value of 0.007 < 0.5, then simultaneously trust and commitment have an effect on increasing customers of PT. Telkomsel Indonesia, this is based on the value of f-value > f-table (6.595 > 3.34) with significance value of 0.005<0.05, then the coefficient of determination was 0.328 or 32.8%. Thus, the percentage effect of trust and commitment toward increasing customer at PT. Telkomsel Indonesia was 32.8% while the remaining of 77.2% was affected by other variables outside this study.